Kritik Konstruksi Relasi Gender dalam Keluarga Islam: Telaah Pemikiran Asma Barlas dan Amina Wadud Muhsin - Nur Anisa , Lina (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2024)
The construction of gender relations in Islamic families has long been dominated by patriarchal interpretations that place women in a subordinate position. Asma Barlas and Amina Wadud Muhsin offer a feminist hermeneutical perspective that highlights the importance of reinterpreting sacred texts to achieve a more egalitarian understanding. This study aims to examine critiques of the construction of gender relations in Islamic families through an analysis of the thoughts of Asma Barlas and Amina Wadud Muhsin. The research method employed is a literature study with a descriptive-analytical approach. Data collection was conducted through a comprehensive literature review, including the major works of Asma Barlas and Amina Wadud Muhsin, as well as related studies that support the analysis. The data analysis technique used is content analysis. The findings reveal that the feminist approach to Islamic exegesis can uncover patriarchal biases, provide more just alternative interpretations, and encourage reforms in Islamic family law. These findings emphasize the need for academic and religious dialogue on gender exegesis, as well as the integration of feminist thought into Islamic education to foster a more inclusive and equitable understanding.